The impact of Instagram influencer marketing in the restaurant industry - Anjos, C. (2022)
When improving their offer, restaurants should also communicate adequately and draw the attention of the public, taking advantage of all available means of communication and opting for the most effective marketing techniques. Therefore, the main objective is to study the six dimensions that encompass a set of digital influencers’ characteristics and to understand if this is actually a communication channel that positively impacts the Portuguese restaurant sector. Using a mixed-method approach, we combined a qualitative study based on a focus group with a survey for a quantitative study. Findings reveal that of the six dimensions of the research model, only one has no impact on the increase of potential clients. In this way, the remaining five are considered to be sufficiently differentiating to arouse consumer interest in visiting restaurants promoted by Instagram influencers.